Asymptotic numerical solver for the linear Klein–Gordon equation with space- and time-dependent mass. (May 2021) - Condon, Marissa; Kropielnicka, Karolina; Lademann, Karolina; Perczyński, Rafał
Abstract: We are concerned with numerical approximation of the linear Klein–Gordon equation with time- and space-dependent mass. We propose an asymptotic-numerical approach as a powerful tool in the presence of very high-frequency oscillations. As we shall show, the proposed method achieves high accuracy with a very low computational cost. A numerical example and comparisons are presented to confirm the efficiency of the approach.